EFFORTS TO IMPROVE BEGINNING READING SKILLS THROUGH THE STRUCTURAL ANALYTICAL SYNTHETIC (SAS) METHOD IN INDONESIAN LANGUAGE LESSONS OF GRADE 1 STUDENTS OF MEKARSARI 2 STATE ELEMENTARY SCHOOL PANIMBANG - Sukmanah; Azmi, Ulil (Journal of Learning on History and Social Sciences, 2024)
Objective: This study aims to improve the Beginning Reading Skills of Grade 1 students at SDN Mekarsari 2 Panimbang in Indonesian Language lessons through the SAS method. Method: This research employed Classroom Action Research based on the Kemmis and Taggart model, consisting of four stages from the pre-cycle to cycle III. Results: In the pre-cycle, the average student evaluation score was 65, with a classical completion rate of 30.4% (11 out of 36 students scored above the minimum passing grade). In cycle I, the average score increased to 71, with a classical completion rate of 52.7% (19 students). Cycle II showed further improvement, with an average score of 83 and a classical completion rate of 89% (32 students). In cycle III, the average score reached 90.5, with a classical completion rate of 95.5% (34 students). Teacher activity scores also improved, from 4.25 in cycle I to 4.46 in cycle II and 4.56 in cycle III. Novelty: This study demonstrates the effectiveness of the SAS method in significantly improving beginning reading skills in Grade 1 students while providing insights into managing classroom action-based learning.